2021
DOI: 10.3390/ijms22168555
|View full text |Cite
|
Sign up to set email alerts
|

The PPARβ/δ-AMPK Connection in the Treatment of Insulin Resistance

Abstract: The current treatment options for type 2 diabetes mellitus do not adequately control the disease in many patients. Consequently, there is a need for new drugs to prevent and treat type 2 diabetes mellitus. Among the new potential pharmacological strategies, activators of peroxisome proliferator-activated receptor (PPAR)β/δ show promise. Remarkably, most of the antidiabetic effects of PPARβ/δ agonists involve AMP-activated protein kinase (AMPK) activation. This review summarizes the recent mechanistic insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Thus, the effects in AMPK and PPARβ/δ activation levels elicit by GSE might be derived by generation of endogenous PPARβ/δ ligands in the liver that might protect against IR, type 2 diabetes mellitus, and its associated disorders. 74 Nevertheless, additional metabolic studies are required in liver and other tissues affected by PPARβ/δ activity (brain, skeletal muscle, adipose tissues, and intestines) to better understand what effects of GSE extract are mediated by PPARβ/δ and what implication have the GSE extract on the AMPK-PPARβ/δ pathway in animal models of IR and metabolic disturbances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the effects in AMPK and PPARβ/δ activation levels elicit by GSE might be derived by generation of endogenous PPARβ/δ ligands in the liver that might protect against IR, type 2 diabetes mellitus, and its associated disorders. 74 Nevertheless, additional metabolic studies are required in liver and other tissues affected by PPARβ/δ activity (brain, skeletal muscle, adipose tissues, and intestines) to better understand what effects of GSE extract are mediated by PPARβ/δ and what implication have the GSE extract on the AMPK-PPARβ/δ pathway in animal models of IR and metabolic disturbances.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the effects in AMPK and PPARβ/δ activation levels elicit by GSE might be derived by generation of endogenous PPARβ/δ ligands in the liver that might protect against IR, type 2 diabetes mellitus, and its associated disorders. 74…”
Section: Food and Function Papermentioning
confidence: 99%
“… 63 Aguilar-Recarte et al reported that metformin lowers glucose through by inhibiting mitochondrial respiratory chain complex 1 and activating AMP-activated protein kinase (AMPK), which has been recognised as a potential IR-related pathway. 64 Similarly, Entezari et al also showed that AMPK signalling improves insulin sensitivity and prevents oxidative stress and cell death in cells. Entezari et al also showed that AMPK signalling improves insulin sensitivity and prevents oxidative stress and cell death in β cells.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, hsa-miR-455-3p can bind abundant target genes, such as APOBEC3F, BAIAP2, CDKN2A, CLCC1, PFKP, PLPP4, POFUT2, SYT7, and TMEM43. Hsa-miR-455 enhances adipogenic differentiation of 3T3-L1 cells by targeting uncoupling protein-1 [ 29 ]. Hsa-miR-455 activates AMPKα1 by targeting HIF1, and AMPK promotes the brown adipogenic program and mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 99%